2001
DOI: 10.1002/1097-0142(20010401)91:7<1332::aid-cncr1136>3.3.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Differing rates of loss of DPC4 expression and of p53 overexpression among carcinomas of the proximal and distal bile ducts

Abstract: These results demonstrate that abnormalities in DPC4 and p53 gene expression are frequent in distal common bile duct carcinomas, just as they are in pancreatic ductal adenocarcinoma, suggesting that these two tumor types might share a similar molecular pathogenesis. They also show that proximal and distal bile duct carcinomas have different patterns of inactivation of tumor-suppressor genes, indicating that they often arise through different molecular mechanisms likely reflecting their differing etiologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 0 publications
1
43
1
Order By: Relevance
“…In two studies of DPC4 protein expression, loss was noted in 55% and 60% of extra-hepatic bile duct carcinomas. However, there was no correlation with survival (17,30).…”
Section: P53 [Table 1]supporting
confidence: 90%
See 2 more Smart Citations
“…In two studies of DPC4 protein expression, loss was noted in 55% and 60% of extra-hepatic bile duct carcinomas. However, there was no correlation with survival (17,30).…”
Section: P53 [Table 1]supporting
confidence: 90%
“…A number of factors may account for these disparities including use of different cut-off values for positivity, antibodies and inclusion of varying anatomical and histological subtypes of CC. Indeed, two studies have noted increasing p53 expression in more distal tumours in comparison to proximal ones when a subanalysis is undertaken (28,30). This may indicate a more important role for p53 overexpression in extra-hepatic, distal bile duct carcinomas.…”
Section: P53 [Table 1]mentioning
confidence: 87%
See 1 more Smart Citation
“…Previously, we showed that loss of Dpc4 expression is as frequent in distal (intrapancreatic) bile duct carcinomas (55%) as it is in pancreatic adenocarcinoma. In contrast, the frequency of Dpc4 loss was lower (overall, 15%) in more proximal (perihilar and intrahepatic) bile duct carcinomas (28). Interestingly, we observed loss of Dpc4 protein in a similar percentage of in situ gallbladder carcinomas associated with invasive carcinomas (2 of 13, or 15%), suggesting that DPC4 inactivation occurs early in these lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of expression is seen in approximately 60% of pancreatic ductal adenocarcinomas, which is associated with poor prognosis. 162,192 SMAD4 loss is also reported in 9.5% of gallbladder adenocarcinomas, 193 50% to 55% adenocarcinomas of extrahepatic bile ducts, 193,194 and 12.5% to 45% intrahepatic cholangiocarcinomas. [193][194][195] CK17.-Cytoplasmic CK17 positivity has been reported in 60% to 88% of pancreatic ductal adenocarcinomas, 162,167,196,197 53% of gallbladder adenocarcinomas, 198 and 59% of adenocarcinomas of extrahepatic bile ducts.…”
mentioning
confidence: 99%